L’activité économique et financière en 1982 - Landry, Jean-Luc (Assurances)

(untitled) (HEC Montréal, 1983)
The principal events of 1982, both in Canada and in the United States, are reviewed and the author draws our attention to the extraordinary fluctuations which disturbed the financial markets in both countries. Along with many other economists, he forecasts an improvement in the U.S. economy for the beginning of 1983, but he wonders to what degree Canada will follow this lead and when a major change will occur here. Any improvement in Canada will probably follow well behind that of our neighbour. When will things get better in Canada? There are no precise statistics or facts to give us the answer, even if some optimists suggest it might be in the course of 1983.